Исследование тяньшанской полевки (Clethrionomis frater Thomas, 1908) в лабораторных условиях - Башенина, Н.В. (Вестник зоологии, 1969)
The interior and exterior peculiarities of Ctethrionomys frater are given in the article. Its growth and development from its birth and to the grown-up state, age and season changes in chemical thermoregulation are described. The data are cited on temperatures under which the basal and critical metabolism takes place, on the duration ol pregnancy, size of droppings. The recommendations on keeping and breeding Clethrionomys frater under laboratory conditions are given.